THE CALCULATION OF THE ATMOSPHERE CHEMICAL POLLUTION AFTER ACCIDENTS IS BASED ON CODE AIR-3 - Biliaiev, M. M. (Science and Transport Progress, 2010)
The basic principles of development of the software AIR-3 aimed at simulation of the atmosphere chemical pollution after accidents are under consideration. The modeling is based on the numerical integration of the K-gradient transport model. The results of numerical experiment are presented.